Philosophical-Ethical Aspects Of Intercultural Interaction Of Youth In The Context Of Globalization - Jaloliddin Eshquvvatov (Periodica Journal, 2026)
The article examines the philosophical and ethical aspects of intercultural interaction among youth in the context of globalization. Particular attention is paid to the analysis of intercultural communication as a form of moral interaction within which value orientations, moral attitudes, and cultural identity of young people are formed. It is demonstrated that under conditions of the intensive expansion of global informational and sociocultural connections, youth emerge as a key subject of intercultural dialogue while simultaneously experiencing the influence of both universal and local values.
Keywords: Intercultural communication; youth; globalization